Influence of rurality, deprivation and distance from clinic on uptake in men invited for abdominal aortic aneurysm screening. Issue 8 (7th May 2015) - Crilly, M. A.; Mundie, A.; Bachoo, P.; Nimmo, F.
Abstract Background Effective abdominal aortic aneurysm (AAA) screening requires high uptake. The aim was to assess the independent association of screening uptake with rurality, social deprivation, clinic type, distance to clinic and season. Methods Screening across Grampian was undertaken by trained nurses in six community and three hospital clinics. Men aged 65 years were invited for screening by post (with 2 further reminders for non‐responders). AAA screening data are stored on a national call–recall database. The Scottish postcode directory was used to allocate to all invited men a deprivation index (Scottish Index of Multiple Deprivation), a Scottish urban/rural category and distance to clinic. Multivariable analysis was undertaken. Results The cohort included 5645 men invited for screening over 12 months (October 2012 to October 2013); 42·6 per cent lived in urban areas, 38·9 per cent in rural areas and 18·5 per cent in small towns (uptake 87·0, 89·3 and 90·8 per cent respectively). Overall uptake was 88·6 per cent with 76 new AAAs detected: 15·2 (95 per cent c.i. 11·8 to 18·6) per 1000 men screened. Aberdeen city (large urban area) had the lowest uptake (86·1 per cent). Uptake declined with increasing deprivation, with the steepest decline in urban areas. On multivariable analysis, a 1‐point increase in deprivation deciles was associated with a 0·08 (95 per cent c.i. 0·06 to 0·11) reduction in the odds of being screened (P < 0·001). Clinic type (community versus hospital), distance to clinic and season were not associated independently with uptake. Conclusion Both urban residence and social deprivation were associated independently with uptake among men invited for AAA screening.